2018
DOI: 10.1136/bmjopen-2018-023579
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of how women in the UK perceive the provision of care received in an early pregnancy assessment unit: an interpretive phenomenological analysis

Abstract: ObjectiveThe objective of the study was to explore how women experience care within an early pregnancy assessment unit (EPAU) and how they are helped to understand, reconcile and make sense of their loss and make informed decisions about how their care will be managed following a first trimester miscarriage.DesignThis was a single centre, prospective qualitative study. An interpretive phenomenological analysis approach was used to interpret the participants’ meanings of their experiences. It is an ideographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(68 citation statements)
references
References 37 publications
1
60
0
Order By: Relevance
“…Twenty‐four were in expectant parents and four were in HCPs. These were published between 1994 25 and 2018 26,27 and included 637 participants (581 expectant parents/56 staff). HCPs were obstetricians, 26,28 nurses and midwives 29 and sonographers 30 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty‐four were in expectant parents and four were in HCPs. These were published between 1994 25 and 2018 26,27 and included 637 participants (581 expectant parents/56 staff). HCPs were obstetricians, 26,28 nurses and midwives 29 and sonographers 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported ethnicity data. In two, all participants were White, 38,40 in two, >90% of participants were White 10,36 and in three, >10% of participants were from a non‐White ethnic group 27,37,39 . Most studies used qualitative interviews (n = 23) and five used mixed methods 25,30,31,39,40 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations